Analysis Motivation Work and Environment Work to Employee Engagement Through Employee Organizational Commitment PT. Asam Jawa - Purnomo, Eko; Suhairi, Suhairi; Harahap, Muhammad Ikhsan; Samad, Khairunnisa Abd (SENTRALISASI, 2025)
This study analyzes work motivation and work environment that affect employee engagement through organizational commitment. This study uses an ex post facto research approach in a quantitative model. Survey data collection with a sample of 293 employees from a total of 1090 employees of PT Asam Jawa was carried out through observation techniques, interviews, and distribution of special questionnaires with a Likert scale. Data analysis used path analysis through two stages, namely measurement model analysis (outer model) and structural model analysis (inner model), assisted by Smart PLS software version 4.1.0.3. The results of the study indicate that work motivation has a significant effect on employee engagement at PT Asam Jawa. The work environment has a significant effect on employee engagement at PT Asam Jawa. Work motivation has a substantial effect on organizational commitment at PT Asam Jawa. Organizational commitment has a significant effect on employee engagement at PT Asam Jawa. Work motivation has a substantial effect on employee engagement at PT Asam Jawa. The work environment has a significant effect on employee engagement at PT Asam Jawa.